rTMS Therapy Reduces Hypofrontality in Patients With Depression as Measured by fNIRS - Kawabata, Yasuo; Imazu, Shin-ichi; Matsumoto, Koichi; Toyoda, Katsunori; Kawano, Makoto; Kubo, Yoichiro; Kinoshita, Shinya; Nishizawa, Yoshitaka; Kanazawa, Tetsufumi (Frontiers in Psychiatry, 2022)
Multichannel functional near-infrared spectroscopy (fNIRS) is a tool used to capture changes in cerebral blood flow. A consistent result for depression is a decrease in blood flow in the frontal cortex leading to hypofrontality, which indicates multidomain functional impairment. Repetitive transcranial magnetic stimulation (rTMS) and elective convulsive therapy (ECT) are alternatives to antidepressant drugs for the treatment of depression but the underlying mechanism is yet to be elucidated. The aim of the current study was to evaluate cerebral blood flow using fNIRS following rTMS treatment in patients with depression. The cerebral blood flow of 15 patients with moderate depression after rTMS treatment was measured using fNIRS. While there was clear hypofrontality during pre-treatment (5±2.5), a notable increase in oxygenated hemoglobin was observed after 30 sessions with rTMS (50±15). This increased blood flow was observed in a wide range of channels in the frontal cortex; however, the centroid values were similar between the treatments. Increased blood flow leads to the activation of neuronal synapses, as noted with other neuromodulation treatments such as electroconvulsive therapy. This study describes the rTMS-induced modulation of blood oxygenation response over the prefrontal cortex in patients with depression, as captured by fNIRS. Future longitudinal studies are needed to assess cerebral blood flow dynamics during rTMS treatment for depression.